Art and Artist Movement in Banten Edi Bonetski X PengPeng - Gisela Anindita (Graduate School of Institut Seni Indonesia Yogyakarta, 2020)
Banten is one of the provinces in Indonesia. It is located in the westernmost of Java. Art Movement in Banten is not as famous as Jakarta, Yogyakarta, nor Bali. Being an Artist is not the most famous, not even an option for Banten's job or career. Being an artist in Banten is because the people are not familiar with the art, especially contemporary art. So being an artist in Banten means also being an educator for social change. Edi Bonetski and PengPeng, both are Banten born and raised artist, are trying to make an art movement in Banten. They are doing what I called